STRATEGI DINAS KEBUDAYAAN DAN PARIWISATA KOTA BANDUNG DALAM MENINGKATKAN PELESTARIAN KESENIAN TRADISIONAL PADA TAHUN 2023 - Tarisa Fitrianti.A.R.; Rahman Mulyawan; Selvi Centia (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
Research on the Strategy of the Bandung City Culture and Tourism Office in increasing the Preservation of Traditional Arts is motivated by the problem of waning public interest in traditional arts. This decline is one of the concerns of the government which has a role in developing, protecting, utilizing and fostering traditional arts. The aim of this research is to improve the preservation of traditional arts in the city of Bandung. Therefore, efforts are needed from the Bandung City Culture and Tourism Department to preserve traditional arts. The method used in this research is a qualitative descriptive approach. Data was obtained through library research and field studies in the form of observations, interviews and documentation studies. Researchers analyze this research through theoretical and legalistic analysis. In this research, researchers found that there were some things that had been optimal and some had not been optimal in efforts to increase the preservation of traditional arts. Judging from the government's strategy stage (Mulgan, 2009), the objective aspect of preserving regional traditional arts is not yet optimal due to limited human resources, from the environmental aspect the contribution of the government and artists is good, but there is a lack of community contribution so it is not optimal, from the direction aspect The government has been optimal in directing increased preservation of traditional arts for arts practitioners and the community. From the action aspect, the government, arts practitioners and the community still feel that it is not optimal because the implementation of arts and development must be improved. From the learning aspect, the evaluation from the previous year is still not implemented optimally. Researchers can conclude that the strategy of the Bandung City Culture and Tourism Office is not optimal in efforts to increase the preservation of traditional arts. Keywords: Government Strategy, Traditional arts